Correlation between CCR7 expression and lymph node metastatic potential of human tongue carcinoma. (14th March 2014) - Xia, X; Liu, K; Zhang, H; Shang, Z
Abstract : Metastasis is an important cause of cancer‐related mortality. In this study, we investigated the role of CCR7 in the lymph node metastasis of tongue carcinoma. Immunohistochemistry and Western blot revealed the expression of CCR7 in tongue SCC tissues and cell lines. In addition, we examined the expression of CCL21, a ligand of CCR7, in normal and diseased lymph nodes using immunohistochemistry and/or real‐time PCR. The CCR7 expression was significantly correlated with cervical lymph node metastasis, tumor staging, and histological grade ( P  =   0.015, 0.040, and 0.015, respectively). The multivariate analysis showed that regional lymph node metastasis, the expression of CCR7, and LVD were the independent poor prognostic factors. Knockdown of CCR7 gene resulted in a significant inhibition of migration and invasion of SCC4 cells in vitro without affecting the proliferation and apoptosis of tumor cells. Also, CCR7 knockdown obviously inhibited cervical lymph node metastasis in an animal tumor model. Our study indicated that CCR7 may play an important role in progression of tongue SCC and could be a promising target for tongue SCC therapy.